The Effectiveness of Using SQ5R Strategy Combined With Poster As Media To Teach Reading Comprehension - Juliani, Nindy Silvi; Chotimah, Ima Chusnul (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This study examines how combining the SQ5R strategy and poster affects students’ reading comprehension. Since the group for this study is not randomly selected, a quasi-experimental design is used. The research subjects are students from a senior high school in Indonesia. The sample was selected using purposive sampling, in which XI-1 became the experimental class, and XI-2 was the control class. The experimental class consisted of 20 students, and the control class consisted of 25 students. The instrument consisted of two written tests; a pre-test and a post-test. Students’ reading comprehension achievement was the dependent variable, and the combination of the SQ5R strategy and poster was the independent variable. An independent sample test was utilized to analyze the data. The result suggests that the combination of the SQ5R strategy and poster was conducive to significantly higher students’ reading comprehension skills, in which the significant value (0.000) was lower than the alpha value (0.005). It can be concluded that the combination of the SQ5R strategy and poster significantly affects students’ reading comprehension skills.